Resenha de SARR, Felwine. 2019. Afrotopia. São Paulo: n-1 edições. - Souza, Aline Cristina Campos de (Revista de Antropologia da UFSCar, 2022)
Resenha de SARR, Felwine. 2019. Afrotopia. São Paulo: n-1 edições.